“INTERNATIONAL MARKETING STRATEGIES OF MSME’s-WITH SPECIAL REFRENCE WITHEXPORTING FIRMS” - Kumar, Sunil; Dubey, Prince; Siddiquei, Mohd Imran; Muneeb, Syed Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Purpose-The intent of this paper is to spotlight the marketing strategies of Micro, Small and Medium scale exporting firms to identify the factors related to the international marketing in Indian context as well as to identify most dominating constituent factors of international marketing strategy. Design/Methodology/Approach- In the present study we have used convenience sampling in order to get more insight about the research issue in the concern context. In our study there are 48 respondents who are SMEs exporters where SMEs of Leather 25 and Glass 23.In sample units, we concern to Exporters to get the response by mangers, directors, assistance managers or any person who relate to the export control process and used factor analysis. Findings- In research we had studied the marketing strategies of the exporting firms to take decision in the regard of exporting and found factors which helps MSME’s to export their products in international market. Originality/Value- Notable number of research and surveys has been conducted on marketing strategies of different firms but MSME’s are the base for economic development and have a major share in providing employment as well as they covers a huge part of exports through various marketing strategy.